Research on the Integrated Green Development Strategy of Coal and Co-existed and Associated Resources - Hongpu Kang; Heping Xie; Shuangming Wang; Shihua Ren; Yaning Zhang; Baoqiang Wang; Peipei Chen; Xiaomiao Jiao; Dezhi Zheng; Yanghui Ren; Yuedong Liu (中国工程科学)
Coal is the cornerstone of China’s energy security. There are many types and wide distributions of coal associated resources, with abundant reserves and high utilization value. Promoting the integrated green development of coal and associated resources is an inevitable requirement for improving the efficiency of resource development and utilization, accelerating the green transformation of development mode, and ensuring national resource security in the new era. This article clarifies the combination types, distribution and typical resources of coal and associated resources. The technological maturity of coal and associated resource development has been analyzed. Four typical development models of coal and associated resource technology integration, development subject integration, management integration, and industrial chain integration have been analyzed. The development benefits in terms of economy, security, and ecology have been evaluated and the key problems currently existing have been summarized. On this basis, a strategic blueprint for the integrated green development of coal and associated resources in China has been depicted, the “three-step” strategic goal has been proposed, the integrated green development technology system covering integrated digital survey and design technology, safe and efficient collaborative development technology, and intelligent green low-carbon technology has been constructed, and the strategic path framework of “four advances, one exploration” has been constructed. Finally, policy recommendations have been put forward to promote the integrated green development of coal and associated resources, including improving the mining rights management system, forming a joint exploration and mining mechanism, increasing investment in scientific and technological innovation, and establishing a coordinated exploration and development incentive mechanism.